2021
DOI: 10.1590/fst.38219
|View full text |Cite
|
Sign up to set email alerts
|

Row orientation effects on chemical composition and aromatic profile of Syrah winter wines

Abstract: Sunlight and heating influence leaf and grape metabolism and therefore wine quality. As a recent management tool, no information exists on the effects of grapevine row orientation on the wine composition of Syrah vines within the context of double pruning management, a technique used to transfer the grape harvest from the wet summer to the dry winter season. This is a first attempt to investigate the wine composition from north-south-(NS) and east-west-(EW) oriented Syrah winter vines. EW wine samples had high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…In general, the climatology of the year and the vine plant location (subplot) highly condition the effectiveness of the biostimulant application, especially in the water use efficiency and yield-related parameters. In this regard, it has been reported that the position of the subplot and especially the row orientation could condition physiological functioning [64] and the metabolic profile [65]. In our study, the physiology-related parameters and yield quantity were more affected in A than B.…”
Section: Discussionmentioning
confidence: 44%
“…In general, the climatology of the year and the vine plant location (subplot) highly condition the effectiveness of the biostimulant application, especially in the water use efficiency and yield-related parameters. In this regard, it has been reported that the position of the subplot and especially the row orientation could condition physiological functioning [64] and the metabolic profile [65]. In our study, the physiology-related parameters and yield quantity were more affected in A than B.…”
Section: Discussionmentioning
confidence: 44%
“…the synthesis of anthocyanins and procyanidins, and increase the phenolic maturity of grapes (Mota et al, 2021;Zhang et al, 2021). Application of exogenous abscisic acid can increase the content of proanthocyanidins in wine grapes and enhance the oxidative capacity of wine (Xi et al, 2013).…”
Section: Effects Of Foliar Iron Spraying On Cabernet Sauvignon Phenol...mentioning
confidence: 99%
“…Butyrolactone and beta-damascenone were found in the east-west group. The orientation of the variety had a significant effect on the chemical composition and aroma profile (Mota et al, 2021).…”
Section: Introductionmentioning
confidence: 99%